Existence And Strategy Of The Deputy Head Of Madrasah in The Field of Student Affairs In Fostering The Activities Of The Madrasah Intra Student Organization - Fatimah Kurniawati; Triono Ali Mustofa (Al-Fikru)
Student organizations provide a space for students to build competencies and characters that are not found in the classroom. However, this organization is often neglected and not managed properly. With regard to that, this study aims to analyze the existence of the vice principal for student affairs in fostering the activities of the Madrasah Intra Student Organization at Madrasah Tsanawiyah Negeri Surakarta 1. The research method used is qualitative based on phenomenological studies. Data collection techniques using observation, interviews and documentation studies. The result is the existence of the deputy head of madrasah in the field of student affairs in fostering the madrasah intra student organization is as a manager, leader, innovator, motivator, coordinator. The role has been carried out well and effectively. This can be seen from the ability to empower student organization administrators to carry out work programs well, smoothly, and productively, as well as being able to provide regular guidance and assistance to student organization administrators when they run programs and activities, and can realize the vision and mission of student organizations.